Sustaining Interaction through Group Work In English Foreign Language Classroom - Tahrun Tahrun (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2019)
The purpose of teaching and learning English as a foreign language in Indonesia is to enable the learners to use English for communication in various contexts. To promote communication in teaching and learning activities, the teachers should be able to initiate interaction. To initiate interaction, the teachers may use questions, by which the teachers should consider the appropriate types of question that match with the students. In addition, the teachers should be able to maintain or sustain the interaction in their teaching and learning context. One of the activities which are effective to sustain interaction in the process of teaching and learning is group work. By using group work, the learners are encouraged to interact in English communicatively. Besides, this method increases students' motivation in learning. This is as the effect of learning climate which offers freedom for the students to express their ideas, feeling or criticism freely in front of their group's members.  In addition, group work promotes students' learning responsibility and autonomy. Each member of the groups must be responsible to achieve their common goal. Considering those ideas, group work can be one of the effective methods to sustain interaction in the EFL classroom.